Comprehensive analysis of different grades of roasted-sesame-like flavored Daqu. Issue 1 (1st January 2019) - Fan, Guangsen; Fu, Zhilei; Teng, Chao; Wu, Qiuhua; Liu, Pengxiao; Yang, Ran; Minhazul, Karim a H M; Li, Xiuting
ABSTRACT: We identified physicochemical, volatile compound, and microbial community differences between three grades of roasted-sesame-like flavored Daqu . The Daqu grades had different physicochemical characteristics. The concentrations and proportions of various esters reflected sensory evaluations of the Daqu classes but no rule linking the flavor compound types and concentrations to Daqu grade was identified. The prokaryotic microorganism communities were similar in premium- and first-grade Daqu but very different in general-grade Daqu . The eukaryotic microorganism communities in premium- and general-grade Daqu were similar, but the genus abundances were more similar in the premium- and first-grade Daqu samples than in premium- and general-grade Daqu .